Strategies For The Treatment Of Chronic Bronchitis In Children, Taking Into Account Sexual Development - Oliya Sharipova; Sherzod Bakhronov (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
A study was carried out to study the characteristics of sexual development and measures of secondary prophylaxis in patients with chronic bronchitis. The study included 84 children with chronic bronchitis aged 10 to 16 years. Of them, 37 (44%) are girls and 47 (56%) are boys. Moderate - severe course of the disease was revealed in 43 (51,2%) children, severe - in 41 (48,8%). It was revealed that chronic bronchitis adversely affects the sexual development of children of both sexes. The pace of development of secondary sexual characteristics occurs gradually and does not complete until the end of puberty. The comprehensive stage-by-stage secondary prophylaxis we proposed for children with chronic bronchitis disease contributed to the improvement of both the underlying disease and sexual development.